Artificial intelligence and project management: Exploring the contributions and implications - Pereira, L.; Nobre, R.; Dias, Á.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Logistics Systems and Management, 2024)
With the exponential advancement of technology, most companies are starting to adopt these innovative systems to improve their performance and a major player in this advancement is artificial intelligence (AI). This research explores the application of AI in project resource management in order to understand how this technology can support and improve the management of human and physical resources in projects. The study was conducted through the application of a questionnaire divided into three sections, and it was obtained 127 valid responses with a confidence level of 95%. By taking a sample of professional project managers, it was identified their major difficulties in different project management processes and the main benefits of AI, in particular, the way they manage resources in projects. It was possible to understand that most project managers had relevant difficulties in human resource management and physical resource acquisition; most of them were solved with AI technologies.